Neville Figgis, CR: his life, thought and significance - Avis, Paul (Anglican-Episcopal theology and history, 2021)
Foreword -- Preface -- Notes on Contributors -- John Neville Figgis: A Timeline of His Life and Major Publications -- 1 The Life and Death of John Neville Figgis, C.R -- Mark D. Chapman -- 2 Figgis as a Public Intellectual -- Peter Sedgwick -- 3 Figgis and the Religious Roots of Modern Conservatism -- Jeremy Morris -- 4 The Figgistorians or Anti-Whig Historians of Political Thought -- James Alexander -- 5 'My Kingdom is not of this World': J. N. Figgis and the Politics of England's Religious Past -- Robert G. Ingram -- 6 The Ecclesiology of John Neville Figgis, C.R -- Paul Avis -- 7 Figgis and Nietzsche on Freedom, Authority, and Pluralism -- Andrew Grosso -- 8 John Neville Figgis and William Temple: A Common Tradition of Anglican Social Thought? -- Stephen Spencer -- 9 Without Privilege, without Prejudice: The Resurgence of Religion and the Dilemmas of Secular Liberalism -- Elaine Graham -- 10 Figgis, Families, and Synodality -- Ephraim Radner -- 11 The Road Not Taken: Figgis, Subsidiarity, and Catholic Social Teaching -- William T. Cavanaugh -- 12 Brother Neville: Figgis the Monk -- Thomas Seville, CR -- Index.